2019
DOI: 10.1097/dbp.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Young Children With Gender Nonconforming Behaviors and Preferences

Abstract: Background: There is growing awareness and exposure in both the medical community and the lay media about the characteristics and complex needs of individuals who believe that their gender identity does not match their birth sex. Despite research and lay publications about teens with gender dysphoria and those who identify as transgender, little guidance is available regarding young (prepubertal) children with questions about their gender identity. Although many terms are used to describe these chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Our findings support those of previous studies that highlight the importance of providing mental health services to TGNC youth. 2,5,15,16 We were unable to collect data on comorbid psychiatric conditions, but others have documented a high prevalence of psychopathology in this population. Studies have found that TGNC youth often have higher rates of depression, anxiety, self-harm, and substance use compared with their cisgender counterparts.…”
Section: Figurementioning
confidence: 94%
See 3 more Smart Citations
“…Our findings support those of previous studies that highlight the importance of providing mental health services to TGNC youth. 2,5,15,16 We were unable to collect data on comorbid psychiatric conditions, but others have documented a high prevalence of psychopathology in this population. Studies have found that TGNC youth often have higher rates of depression, anxiety, self-harm, and substance use compared with their cisgender counterparts.…”
Section: Figurementioning
confidence: 94%
“…The burden of this dysphoria may be decreased by delaying puberty. 5,15,16 Providers in our clinic initiate hormone blockers and cross-sex hormones when patients have started puberty, which is determined by either a score of 2 on the Tanner Scale during physical examination or laboratory confirmation. Decisions surrounding when to initiate blockers and/or cross-sex hormone therapy are made by the health care team on an individualized, patient-directed basis.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Some articles repeated what the two articles claimed—that there are no differences in depression or self-worth between transgender children and control children with only slight or minimal differences in anxiety. Turban (2017, 101) stated clearly that “Transgender youth in this study showed only mildly increased levels of anxiety (below the subclinical range)” and that “child-report levels of self-worth were similar to those of matched non-transgender controls.” Chen et al (2018, 76) noted that “Results show that transgender children did not differ from either control group on depression scores and had only marginally higher anxiety scores” and the two groups did not differ “on ratings of depression or self-worth and had marginally higher anxiety scores.” Other studies came to similar conclusions regarding either or both of the two articles (Alberse et al 2019, 389; Alegria 2018, 132; Bonifacio et al 2019, e72; Campo-Engelstein 2019, 85; Cartaya and Lopez 2018, 47; Chen, Hidalgo, and Garofalo 2017, 342; Deardorff et al 2019, 143; Janicka and Forcier 2016, 33; Oswalt and Lederer 2017, 7; Reilly et al 2019; Saleem and Rizvi 2017, 3; Shumer 2018, 1; Toomey, Syvertsen, and Shramko 2018, 7; Valdiserri et al 2019, 579; Wanta and Unger 2017, 126).…”
Section: Discussionmentioning
confidence: 64%